Visions of British Culture from the Reformation to Romanticism The Protestant Discovery of Tradition - Savonius-Wroth, Celestina (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is a major new contribution to the study of cultural identities in Britain and Ireland from the Reformation to Romanticism. It provides a fresh perspective on the rise of interest in British vernacular (or "folk") cultures, which has often been elided with the emergence of British Romanticism and its Continental precursors. Here the Romantics' discovery of and admiration for vernacular traditions is placed in a longer historical timeline reaching back to the controversies sparked by the Protestant Reformation. The book charts the emergence of a nuanced discourse about vernacular cultures, developing in response to the Reformers' devastating attack on customary practices and beliefs relating to the natural world, seasonal festivities, and rites of passage. It became a discourse grounded in humanist Biblical and antiquarian scholarship; informed by the theological and pastoral problems of the long period of religious instability after the Reformation; and, over the course of the eighteenth century, colored by new ideas about culture drawn from Enlightenment historicism and empiricism. This study shows that Romantic literary primitivism and Romantic social thought, both radical and conservative, grew out of this rich context. It will be welcomed by historians of early modern and eighteenth-century Britain and those interested in the study of religious and vernacular cultures. Celestina Savonius-Wroth is Assistant Professor, History Librarian, and Head of the History, Philosophy, and Newspaper Library at the University of Illinois at Urbana-Champaign, USA. She holds a doctorate in British history from Indiana University Bloomington.
1. Introduction -- 2. Ritual, Ceremony, and Custom in the Aftermath of the British Reformations -- 3. "Remaines of Gentilisme and Judaism": Erudition, Polemic, and Apologetics in the Study of British Customs -- 4. The Antiquities of the Common People -- 5. Embodied Religion in Eighteenth-Century Britain: "All Mankind Are the Vulgar in This Respect" -- 6. Religion in the Bardic Revival -- 7. Against the Cold Calculus of Modernity -- 8. Conclusion.
Keywords: Great Britain-History.; Religion-History.; Civilization-History.; Social history; History of Britain and Ireland; History of Religion; Cultural History; Social History